Current Status and Analysis of the Solution of Greening in the Textile Industry in Vietnam - Phan, Thanh Nhan; Le, Song Thanh Quynh (The Indonesian Institute of Science and Technology Research, 2025)
Textile and garment production is one of the essential industries contributing to creating jobs for millions of workers and providing Vietnam's leading source of GDP revenue. The production process of the textile industry also has many impacts on the economy, society, and the environment, not only in Vietnam but also in most countries around the world. In the textile and Garment industry, freshwater consumption accounts for nearly 4%, and water pollution accounts for about 20% worldwide. According to the Vietnam Textile and Apparel Association, the energy consumption of textiles accounts for up to 8% of the energy consumption compared with the energy of the entire industry. It emits about 5 million tons of CO2 per year. Therefore, solutions to green the textile industry, such as designing and building factories in a green and sustainable direction, lighting solutions, optimal production process systems, using energy-saving equipment, and alternative forms of renewable energy are some of the leading critical factors to reducing energy consumption would be analyzed, evaluated and provided optimal solutions for the goal of greening in the textile industry and progress towards the target of net zero emissions by 2050.